1989
DOI: 10.3109/00016488909127487
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Acute Otitis Media:A Prospective Study of Children during the First Three Years of Life

Abstract: To evaluate possible risk factors for developing recurrent acute otitis media (rAOM), 113 children were followed prospectively from birth to the age of 3 years. One of the aims was to determine whether such risk factors could be identified before the onset of the recurrences, so that optimal care and prophylactic measures could be made available at an early stage in such cases, on the basis of continuous follow-up by an ENT specialist. During the follow-up, 13 children developed rAOM, defined as six or more ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
1
6

Year Published

1993
1993
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(90 citation statements)
references
References 13 publications
5
78
1
6
Order By: Relevance
“…Rhinitis is an important risk factor for AOM (Maynard 1969, Henderson et al 1982, Fleming 1987, Harsten et al 1989, Arola et al 1990, Alho et al 1990, Ruuskanen et al 1991, Aniansson et al 1994, Daly et al 1999. In this study significantly more AOM children (87%) reported rhinitis than controls (25%) (p < 0.001).…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Rhinitis is an important risk factor for AOM (Maynard 1969, Henderson et al 1982, Fleming 1987, Harsten et al 1989, Arola et al 1990, Alho et al 1990, Ruuskanen et al 1991, Aniansson et al 1994, Daly et al 1999. In this study significantly more AOM children (87%) reported rhinitis than controls (25%) (p < 0.001).…”
Section: Discussionmentioning
confidence: 46%
“…In 2,750 pairs of Norwegian adult monozygotic and heterozygotic twins Kvaerner et al (1997a) estimated that the variation in liability for recurrent ear infections consisted of 74% heritability in females and 45% in males. URTI's have been claimed to be the most powerful risk factor associated with OM (Maynard 1969, Fleming et al 1987, Harsten et al 1989, Arola et al 1990, Alho et al 1990, Aniansson et al 1994, Daly et al 1999. Eustachian tube dysfunction as a cause of immaturity or anatomical factors has also been shown to be of importance (Doyle 1977, Shapiro 1987, Maw et al 1991, Stenstrom et al 1991.…”
Section: Aimsmentioning
confidence: 99%
“…13,30,31 Girls were overrepresented in the group of children who suffered from Ն4 AOM episodes when compared with the children who had 2 to 3 AOM episodes. Children under the age of 4 were more likely to have had Ն4 AOM episodes in the previous year than older children.…”
Section: Tnfa Promoter Genotypes ؊238 G/g and ؊376 G/g And Tlr4 299 Dmentioning
confidence: 94%
“…In contrast to previous studies, our study only included patients with recurrent AOM and no age-matched controls without otitis were included. 30,42 …”
Section: Discussionmentioning
confidence: 99%
“…The annual economic burden of otitis media in the United States is estimated to be at least $5 billion for direct and indirect costs (Gates 1996). COME/ROM has long been recognized to aggregate in families (Teele et al 1980;De Melker and Burke 1988;Harsten et al 1989;Teele et al 1989). The first family study of COME/ROM (Daly et al 1996) demonstrated that first-degree relatives (parents and siblings) of probands with COME/ROM had greater than expected rates of OM based on population rates.…”
Section: Introductionmentioning
confidence: 99%